Undifferentiated connective tissue disease: state of the art on clinical practice guidelines. (26th February 2019) - Antunes, Margarida; Scirè, Carlo Alberto; Talarico, Rosaria; Alexander, Tobias; Avcin, Tadej; Belocchi, Chiara; Doria, Andrea; Franceschini, Franco; Galetti, Ilaria; Govoni, Marcello; Hachulla, Eric; Launay, David; et al.
Abstract : The term 'undifferentiated connective tissue disease' (UCTD) is generally used to describe clinical entities characterised by clinical and serological manifestations of systemic autoimmune diseases but not fulfilling the criteria for defined connective tissue diseases (CTDs). In this narrative review, we summarise the results of a systematic literature research, which was performed as part of the ERN ReCONNET project, aimed at evaluating existing clinical practice guidelines (CPGs) or recommendations. No specific CPG on UCTD were found, potential areas of intervention are absence of a consensus definition of UCTD, need for specific monitoring and therapeutic protocols, stratification of UCTD based on the risk of developing a defined CTD and preventive measure for the future development of a more severe condition. Patients feel uncertainty regarding the name of the disease and feel the need of a better education and understanding of these conditions and its possible changes over time.